Παρεμβάσεις που βελτιώνουν τον ύπνο σε ασθενείς σε Μονάδες Εντατικής Θεραπείας - Παπαγεωργίου, Χριστίνα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Introduction: Sleep among critically ill patients in the ICU is often interrupted and disturbed causing various problems in their health, their subsequent treatment, and delaying their convalescence. Aim: The purpose of this systematic bibliographic review is to investigate non-pharmacological interventions that nurses may easily apply in an attempt to improve the sleep of critically ill adults, who are treated in intensive care units. Material and Method: The method used in this case was the search of relative Greek and international bibliography in the databases of PubMed and CINAHL, with keywords. The inclusion criteria include the type of the intervention: use of earplugs, eye masks, white noise and relaxing music. The main variables were the quality and quantity of sleep. Results: The search has ended up in 10 studies during the period 2009-2017, which fulfilled the present criteria. Within the search of bibliography, it was optimized that the use of inducing sleep music, white noise, earplugs and eye masks improved the quality and quantity of sleep of critically ill patients in intensive care units. Conclusions: All these interventions that improve sleep, contribute, at the same time, towards an improvement of the quality of nursing care, in the psychology, communication and breathing, reduction of pain, improvement of circadian rhythm and improvement of the immune system, in a better convalescence and progress of the patients in the intensive care units. As a result, beyond the improved outcomes for the patients, the workload, the cost of care and readmission numbers are reduced.
Keywords: Icu; Sleep; Interventions; Nursing; Systematic review; ΜΕΘ; Ύπνος; Παρεμβάσεις; Νοσηλευτική; Συστηματική ανασκόπηση